USING PATTERNS IN THE FORMATION OF INDEPENDENT JOB FOR STUDENTS FOR LINEAR ALGEBRA. - Radchenko, Sergey (Continuing Professional Education: Theory and Practice, 2019)
The article deals with a specific example of a simple linear algebra method templates which can significantly speed up the process of drafting a separate problems on matrix theory teachers of Mathematics without complex programming environments that require an appropriate level of qualification. This method increases the degree of individualization of tasks to test students’ control, since the number of packages of tasks is not limited possibilities of time and effort the teacher. Thus, the numerical parameters in the generator task allows you to change the level of difficulty to meet the requirement of gradual assimilation of the material. These method have been successfully tested in practice. The results of its use show an increase in students’ autonomy in choosing a method for solving problems of linear algebra. A feature of the proposed method is the synthesis of a compact organization of educational information and flexibility of application. The main idea of the method is to build templates that specify the expected parameters of the solution. A special set of conditions to minimize the complexity of arithmetic and pay more attention to the theoretical material. However, the most important thing - the ability to produce ready-made formulas in TeX editor that let in Moodle environment immediately receive the appropriate image for the package of tasks in linear algebra. The same type of formula, which abound in the task of linear algebra, very difficult replicated in the medium MS Equation Editor, which most users are gaining mathematical formulas text editor MS Word. However, the most important thing - the ability to produce ready-made formulas in TeX editor that let in Moodle environment immediately receive the appropriate image for the package of tasks in linear algebra. The same type of formula, which abound in the task of linear algebra, very badly replicated in the medium MS Equation Editor, which most users are gaining mathematical formulas text editor MS Word. The use of the template method completely eliminates the manual construction of mathematical formulas, replacing the routine operation of the automatic generation of jobs.